Percepção ambiental de estudantes do ensino fundamental sobre práticas ambientais sustentáveis provenientes de duas escolas, urbana e rural, do município de Toledo /Pr - Manfrin, Elisandra Augusta Gafuri (2021)
This study is important for the areas of knowledge related to the environment, as well as for Environmental Education (EE) and its interrelationship with Environmental Sciences and, above all, for thinking about pedagogical strategies and practices in the school environment, helping in the development of students' knowledge about social and environmental issues. The objective is to verify the environmental perception of elementary school students from two State Public Schools in urban and rural areas, in the Municipality of Toledo/PR, in relation to environmental issues related to sustainability. The relevance of the theme and the proposal to scale the results achieved with the various projects aimed at Environmental Education in the school space is justified, from the perspective of a multiplying effect on society. Starting with, some considerations about the research theme and problematic are presented. Then, concepts and history relevant to Environmental Education are demonstrated, as well as the role of schools in teaching environmental education and the challenges, interdisciplinarity, the importance of the teacher as a training agent. The research has in its methodology a qualitative and quantitative approach, with regard to data collection, questionnaires were applied to students, as well as questionnaires to teachers who teach subjects for them. The hypothesis raised was that the theme dealt with in the school environment is discussed in the family nucleus, making the student a propagator of the knowledge transmitted in the school. With this, it is expected a multiplier effect in the society of knowledge and practices in Environmental Education, through the student himself, who, according to the results of this study, it is in the family environment that most of them comment on environmental themes.